Calcitriol promotes the maturation of hepatocyte-like cells derived from human pluripotent stem cells. Issue 211 (July 2021) - Yuan, Fang; Wang, Ning; Chen, Yan; Huang, Xinping; Yang, Zhen; Xu, Yingying; You, Kai; Zhang, Jiaye; Wang, Guodong; Zhuang, Yuanqi; Pan, Tingcai; Xiong, Yue; et al.
Highlights: Calcitriol promoted the functionalities of hPSCs-derived HLCs in P450 activity, urea production, and albumin secretion. Calcitriol enhanced the mitochondrial respiratory capacity of HLCs. Calcitriol induced mitochondrial biogenesis and mitophagy in HLCs. The improvements in HLCs maturation and mitochondrial function by calcitriol were dependent on VDR. Abstract: Human hepatocyte-like cells (HLCs) derived from human pluripotent stem cells (hPSCs) represent a promising cell source for the assessment of hepatotoxicity and pharmaceutical safety testing. However, the hepatic functionality of HLCs remains significantly inferior to primary human hepatocytes. The bioactive vitamin D (VD), calcitriol, promotes the differentiation of many types of cells, and its deficiency is correlated to the severity of liver diseases. Whether calcitriol contributes to the differentiation of HLCs needs to be explored. Here, we found that the supplementation of calcitriol improved the functionalities of hPSCs-derived HLCs in P450 activities, urea production, and albumin secretion. Moreover, calcitriol also enhanced mitochondrial respiratory function with increased protein expression levels of the subunit of respiratory enzyme complexes in HLCs. Further analyses showed that the mitochondrial biogenesis regulators and mitophagy were increased by calcitriol, thus improving the mitochondrial quality. These improvements in functionality and mitochondrial condition were dependent on vitamin D receptor (VDR) because the improvements were abolished under VDR-deficient conditions. Our finding provides a cost-effective chemical process for HLC maturation to meet the demand for basic research and potential clinic applications.